Recent Advances in Biometrics - Sarfraz, Muhammad (IntechOpen, 2022)
Biometrics are widely used in various real-life applications, including personal recognition, identification, verification, and more. They may also be used for safety, security, permission, banking, crime prevention, forensics, medical applications, and communication. This book explores the latest developments, theories, methods, approaches, algorithms, analysis, systems, hardware, and software in biometrics and related systems.